Concrete and steel-concrete composite beam with low hydration heat peak value

By using a concrete formula with low hydration heat peak in steel-concrete combined beams, combined with phase change blockers of paraffin and ferrous nitrate powder and a sustained release additive of β-cyclodextrin coated zinc carbonate, the water in the combined beam is solved. The cracks and crack problems caused by high heat peaks improve the strength and ductility of concrete and extend the service life.

CN119320260APending Publication Date: 2025-01-17ZHEJIANG OUYUE COMM CONSTR TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411352517.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-26
Publication Date
2025-01-17

AI Technical Summary

Technical Problem

Large volume concrete in steel-concrete composite beams is prone to cracks and cracks due to the high peak of hydration heat, resulting in a reduced service life and insufficient ductility, which affects the stability of the structure.

Method used

Using concrete formulas with low hydration heat peaks, including cement, sand, aggregate, fly ash, paraffin and ferric nitrate powder phase change blockers, the hardness is adjusted and nitric acid is slowly released through the mixing of paraffin and ferric nitrate powder. Iron powder is used to reduce the peak of hydration heat, and a sustained release additive coated with β-cyclodextrin is added to extend the hydration reaction time and reduce the peak of hydration heat of concrete.

Benefits of technology

It effectively reduces the peak of concrete hydration heat, reduces the generation of cracks and cracks after pouring, enhances the strength and ductility of concrete, and improves the service life and production efficiency of combined beams.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119320260A_ABST
    Figure CN119320260A_ABST
Patent Text Reader

Abstract

The invention discloses concrete with a low hydration heat peak value and a steel-concrete composite beam, the concrete is prepared from the following raw materials in parts by mass: 300-500 parts of cement, 800-900 parts of sand, 1100-1400 parts of aggregate, 300-350 parts of fly ash, 200-280 parts of water and 45-63 parts of phase change blocking agent, the phase change blocking agent is obtained by mixing and granulating paraffin and ferric nitrate powder, the melting point of the paraffin is 42 + / -2 DEG C, and the melting point of the ferric nitrate powder is 42 + / -2 DEG C. The mass ratio of the paraffin to the ferric nitrate powder is 1: (5-5.4), and a hydration heat curve is smoothed by storing hydration heat and slowing down the hydration heat reaction rate in a short time, so that the hydration heat peak value of the concrete is reduced, the possibility that cracks are generated due to excessive stress in the concrete body when the hydration heat peak value is reached after the concrete is subjected to large-volume pouring is reduced, and the service life of the concrete is prolonged. And the strength of the final concrete can be enhanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to a building composite beam, and in particular to a concrete and steel-concrete composite beam with low hydration heat peak value. Background Art

[0002] Steel-concrete composite beam is a new type of structure developed on the basis of steel structure and concrete structure. It mainly sets shear connectors such as studs, channel steel, bending bars, etc. between the steel beam box and the concrete flange plate, between the steel beam box and the concrete beam plate, to resist the lifting and relative sliding of the two at the interface, so that they can work together as a whole. It is mostly used for rail transit bridges and urban overpass bridges.

[0003] Since the steel-concrete composite beam is made in a long length of 20 to 80m, the corresponding concrete flange plate and beam plate have a large casting volume and a high hydration heat peak. During the curing process, cracks are easily generated in the casting body, resulting in failure of the flaw detection test. Or there are small cracks allowed by the flaw detection test, but the upper limit of the strength of the concrete body will still be reduced. When the seasonal temperature changes, the ductility of the concrete body is insufficient, and shear stress is generated at the joint with the steel beam box, resulting in stress concentration in the concrete. When it is under pressure or impact, the damage is accelerated and the service life is reduced. Summary of the invention

[0004] In order to reduce the problem that large-volume concrete bodies in steel-concrete composite beams are prone to cracks due to high hydration heat peak, and the cracks affect the use of the concrete body, a concrete with low hydration heat peak and a steel-concrete composite beam are provided.

[0005] The above first invention objective of the present invention is achieved through the following technical solutions: A concrete with low hydration heat peak value, comprising the following raw materials in parts by mass: 300-500 parts of cement, 800-900 parts of sand, Aggregate 1100~1400 parts, 300-350 parts of fly ash, 200-280 parts of water, 45-63 parts of phase change blocker, the phase change blocker is obtained by mixing and granulating paraffin wax and ferric nitrate powder, the melting point of the paraffin wax is 42±2°C, and the mass ratio of the paraffin wax to the ferric nitrate powder is 1:(5-5.4).

[0006] By adopting the above technical solution, paraffin wax and ferric nitrate powder serve as excipients for each other, paraffin wax binds and wraps ferric nitrate powder to granulate it, and ferric nitrate powder adjusts the hardness of paraffin wax and reduces its brittleness, thereby preventing the phase change blocker from breaking during the concrete mixing process; The peak value of concrete hydration heat is 50-60℃. During the release of concrete hydration heat, when the concrete temperature is higher than the melting point of paraffin, the paraffin in the phase change blocker melts and stores hydration heat. At the same time, as the paraffin melts, the iron nitrate powder is slowly released through the liquid surface contact. The iron nitrate dissolves in the liquid of the concrete and reacts with calcium hydroxide to produce iron hydroxide precipitation and calcium nitrate, reducing the alkali content in the liquid phase of the concrete and increasing the calcium ion concentration in a short period of time, thereby inhibiting the hydration reaction rate, reducing the hydration heat peak without reducing the total amount of hydration heat, and smoothing the hydration heat curve. In addition, the iron hydroxide precipitation will seal the gaps in the concrete, thereby enhancing the strength of the final concrete; In summary, by storing hydration heat and slowing down the hydration heat reaction rate in the short term to smooth the hydration heat curve, the hydration heat peak of the concrete of the present application is reduced, and the possibility of cracks and fissures caused by excessive stress in the concrete body when the hydration heat peak is reached after large-volume pouring of the concrete of the present application is reduced, and the strength of the final concrete can also be enhanced.

[0007] Optional: The preparation method of the phase change blocker is as follows: Weigh ferric nitrate powder and paraffin powder according to the mass ratio, stir and mix to obtain a mixed raw material; The mixed raw material and hexane are mixed and then ball-milled to obtain a ball-milled slurry; The ball mill slurry is spray dried and granulated to obtain a phase change inhibitor with uniform particle size distribution.

[0008] By adopting the above technical scheme, the ferric nitrate powder is ball-milled in a mixed liquid phase of hexane and paraffin. The mixed liquid phase of hexane and paraffin plays the role of dispersion, lubrication and anti-oxidation, and ferric nitrate powder with small particle size and uniformity can be obtained. At the same time, the ball milling process is also a mixing process, so the preparation method of the phase change inhibitor is also simpler.

[0009] Optional: Ferric nitrate powder with a particle size of 500 nm.

[0010] By adopting the above technical solution, the hardness and granulation of the phase change blocker are better, and the release time and rate of ferric nitrate are better, and the resulting concrete has a low hydration heat peak and higher strength.

[0011] Optionally: the phase change blocker has a particle size of 60 μm.

[0012] By adopting the above technical solution, the phase change blocker is dispersed more evenly and is not easy to be broken during the mixing process of concrete raw materials, and the release time and rate of ferric nitrate are better. The obtained concrete has a low hydration heat peak and higher strength.

[0013] Optionally: 35 to 41 parts of a sustained-release enhancer are also included, wherein the sustained-release enhancer is a core-shell structure, the shell is β-cyclodextrin, and the shell is zinc carbonate.

[0014] By adopting the above technical solution, the slow-release additive of the powder slowly releases β-cyclodextrin first and then releases zinc carbonate. β-cyclodextrin chelates with calcium ions, prolonging the initial setting and final setting time of concrete, extending the window period for the concrete to quickly conduct heat outward before solidification, lowering the temperature of concrete before solidification, reducing the peak value of hydration heat, and thus reducing the possibility of cracks or fissures in large-volume concrete castings; Since the dissolution of β-cyclodextrin in water increases the viscosity of water, it hinders the further dissolution of water, and then can objectively delay the release time of zinc carbonate, so that zinc carbonate is released after the peak of hydration heat; Zinc carbonate can react with calcium hydroxide to reduce the alkali content in concrete, reduce alkali-aggregate reaction, and precipitate calcium ions, thereby reducing the concentration of calcium hydroxide, the hydration reaction product of tricalcium silicate and dicalcium silicate, and thus promoting the hydration reaction; This will reduce the peak heat of hydration of concrete, prolong the duration of the delayed peak, make the hydration reaction thorough, and improve the strength of the concrete.

[0015] Optionally, the mass ratio of β-cyclodextrin to zinc carbonate in the sustained-release aid is 7:(1.8-2.4).

[0016] By adopting the above technical solution, the sustained-release adjuvant has a better effect and the peak value of hydration heat decreases more significantly.

[0017] Optional: Also includes amino water reducer.

[0018] By adopting the above technical solution, the amino water reducer can enhance the fluidity of concrete without changing the water consumption of concrete, which is beneficial to reduce the internal air bubble cavities when pouring large-volume concrete bodies and improve the strength of concrete. At the same time, the amino water reducer can also play a retarding role and reduce the peak value of concrete hydration heat.

[0019] The above second invention objective of the present invention is achieved through the following technical solutions: A steel-concrete composite beam comprises a steel beam box and a concrete beam slab, wherein the concrete is the above-mentioned concrete with low hydration heat peak.

[0020] By adopting the above technical scheme, the hydration heat peak value during the casting process of the beam slab of the steel-concrete composite beam of the present application is low, the generation of internal fine cracks is reduced, the internal structural defects are few, the ductility is good during seasonal temperature changes, and the yield rate is high, the production efficiency is high and the cost is reduced.

[0021] In summary, this application has at least the following beneficial effects: 1. By storing hydration heat and slowing down the hydration heat reaction rate in the short term to smooth the hydration heat curve, the hydration heat peak value of the concrete of the present application is reduced, and the possibility of excessive stress in the concrete body causing cracks and fissures when the hydration heat peak value is reached after the large-volume pouring of the concrete of the present application is reduced, and the strength of the final concrete can also be enhanced; 2. Adding β-cyclodextrin-coated zinc carbonate slow-release additives can reduce the peak hydration heat of concrete, prolong the delayed peak maintenance time, make the hydration reaction thorough, and improve the concrete strength; 3. The steel-concrete composite beam of the present application has a low hydration heat peak during the pouring process of the beam slab, which reduces the generation of small internal cracks, has fewer internal structural defects, and has good ductility during seasonal temperature changes. In addition, the yield is high, the production efficiency is high, and the cost is reduced.

[0022] Instruction Manual Figure 1 This is the cross-section of a steel-concrete composite beam.

[0023] Reference numerals 1. Beam box; 2. Beam slab. DETAILED DESCRIPTION

[0024] raw material The cement is 52.5 ordinary Portland cement.

[0025] The sand is river sand with a particle size of 0.6±0.1mm.

[0026] The aggregate is natural crushed stone aggregate, and the specific particle size grading mass ratio is (5-20mm): (20-40mm): (40-80mm): (80-120mm) = 1:4:3:2.

[0027] The fly ash is a commercially available product of Hebei Huishun Mining Co., Ltd., with a grade of one, a density of 2.54 g / cm3, and a porosity of 63%.

[0028] Paraffin wax is a commercially available product with a melting point of 42±2°C.

[0029] The water reducers include 2-acrylamido-2-methylpropane sulfonic acid and polycarboxylic acid water reducer. 2-Acrylamido-2-methylpropane sulfonic acid is a product of Hubei Xinyuhong Biomedicine Technology Co., Ltd., and the polycarboxylic acid water reducer is CP1200, a product of Nanjing Xinyi Synthetic Technology Co., Ltd.

[0030] Ferric nitrate powder, β-cyclopentane and zinc carbonate powder are commercially available industrial grade products.

[0031] Preparation Example 1 A phase change blocking agent is a particle formed by mixing ferric nitrate powder and paraffin, and the particle size is 60 μm.

[0032] The specific preparation method is as follows: Weigh ferric nitrate powder and paraffin powder with a melting point of 42±2°C in a mass ratio of 5.2:1, stir and mix to obtain a mixture, add 40kg of hexane to 62kg of the mixture, and ball-mill in a ball mill until the ferric nitrate powder has a particle size of 500nm to obtain a ball-milled slurry; spray-dry the ball-milled slurry to granulate to obtain a phase change inhibitor with a particle size of 60μm.

[0033] Preparation Example 2 A phase change blocker, which differs from Preparation Example 1 in that the mass ratio of ferric nitrate to paraffin in the mixture is 1:3.

[0034] Preparation Example 3 A phase change blocker, which differs from Preparation Example 1 in that the mass ratio of ferric nitrate to paraffin in the mixture is 1:5.

[0035] Preparation Example 4 A phase change blocker, which differs from Preparation Example 1 in that the mass ratio of ferric nitrate to paraffin in the mixture is 1:5.4.

[0036] Preparation Example 5 A phase change blocker, which differs from Preparation Example 1 in that the mass ratio of ferric nitrate to paraffin in the mixture is 1:8.

[0037] Preparation Example 6 A phase change blocker, which differs from Preparation Example 1 in that the preparation method is as follows: 52 kg of ferric nitrate powder was mixed with 40 kg of hexane, and then ball-milled, filtered, and dried to obtain ferric nitrate powder with a particle size of 500 nm; 10 kg of paraffin wax was melted and mixed evenly with 52 kg of 500 nm iron nitrate powder, and the particles were granulated and then crushed until the particle size was 60 μm to obtain a phase change blocker.

[0038] Preparation Example 7 A phase change blocker, which is different from Preparation Example 1 in that the particle size of the ferric nitrate powder in the ball milling slurry is 300 nm.

[0039] Preparation Example 8 A phase change blocker, which is different from Preparation Example 1 in that the particle size of the ferric nitrate powder in the ball milling slurry is 800 nm.

[0040] Preparation Example 9 A phase change blocker is disclosed, which is different from the one prepared in Preparation Example 1 in that the particle size of the phase change blocker obtained during ball milling slurry spraying is controlled to be 20 μm.

[0041] Preparation Example 10 A phase change blocker is disclosed, which is different from Preparation Example 1 in that the particle size of the phase change blocker obtained during ball milling slurry spraying is controlled to be 100 μm.

[0042] Preparation Example 11 A sustained-release auxiliary agent has a core-shell structure, wherein the shell is beta-cyclodextrin and the core is zinc carbonate.

[0043] The specific preparation method is as follows: 8.2 kg of β-cyclodextrin, 2.1 kg of 10 μm zinc carbonate powder, and 15 kg of 56 wt % ethanol solution were mixed evenly, stirred for 3 hours, insoluble matter was filtered out, and dried to obtain a sustained-release adjuvant.

[0044] The obtained sustained-release aid weighed 9.1 kg.

[0045] Preparation Example 12 A sustained-release auxiliary agent has a core-shell structure, wherein the shell is beta-cyclodextrin and the core is zinc carbonate.

[0046] The specific preparation method is as follows: 8.2 kg of β-cyclodextrin, 2.4 kg of 10 μm zinc carbonate powder, and 15 kg of 56 wt % ethanol solution were mixed evenly, stirred for 3 hours, insoluble matter was filtered out, and dried to obtain a sustained-release adjuvant.

[0047] The obtained sustained-release aid weighed 9.4 kg.

[0048] Preparation Example 13 A sustained-release auxiliary agent has a core-shell structure, wherein the shell is beta-cyclodextrin and the core is zinc carbonate.

[0049] The specific preparation method is as follows: 8.2 kg of β-cyclodextrin, 1.8 kg of 10 μm zinc carbonate powder, and 15 kg of 56 wt % ethanol solution were mixed evenly, stirred for 3 hours, insoluble matter was filtered out, and dried to obtain a sustained-release adjuvant.

[0050] The obtained sustained-release aid weighed 8.8 kg.

[0051] Preparation Example 14 A sustained-release auxiliary agent has a core-shell structure, wherein the shell is beta-cyclodextrin and the core is zinc carbonate.

[0052] The specific preparation method is as follows: 8.2 kg of β-cyclodextrin, 1.2 kg of 10 μm zinc carbonate powder, and 15 kg of 56 wt % ethanol solution were mixed evenly, stirred for 3 hours, insoluble matter was filtered out, and dried to obtain a sustained-release adjuvant.

[0053] The obtained sustained-release aid weighs 8.2 kg.

[0054] Preparation Example 15 A sustained-release auxiliary agent has a core-shell structure, wherein the shell is beta-cyclodextrin and the core is zinc carbonate.

[0055] The specific preparation method is as follows: 8.2 kg of β-cyclodextrin, 2.8 kg of 10 μm zinc carbonate powder, and 15 kg of 56 wt % ethanol solution were mixed evenly, stirred for 3 hours, insoluble matter was filtered out, and dried to obtain a sustained-release adjuvant.

[0056] The obtained sustained-release aid weighed 9.8 kg.

[0057] Example 1 The invention discloses concrete with low hydration heat peak value, whose raw materials are cement, sand, aggregate, fly ash, water, phase change blocking agent, slow-release auxiliary agent and water reducing agent.

[0058] The phase change blocker is prepared in Preparation Example 1, the sustained-release aid is prepared in Preparation Example 11, and the water reducer is 2-acrylamido-2-methylpropanesulfonic acid.

[0059] The preparation method is as follows: Mix 21 kg of water reducer with 2540 kg of water to make mixing water; The mixing water is then stirred and evenly mixed with 4500kg of cement, 8800kg of sand, 13200kg of aggregate, 3380kg of fly ash, 600kg of phase change blocker and 380kg of slow-release additive to obtain concrete with low hydration heat peak.

[0060] Embodiments 2 to 14 A concrete with low hydration heat peak value is different from Example 1 in that the amount of raw materials is different or part of the raw material sources are different, and the specific differences are shown in Table 1 below.

[0061] Table 1. Raw material sources and dosage records of Examples 1 to 14 Embodiment 15 A concrete with low hydration heat peak value, which is different from Example 1 in that no slow-release additive is added to its raw materials, that is, the amount of slow-release additive is 0.

[0062] Example 16 A concrete with low hydration heat peak value, which is different from Example 1 in that its raw material water reducer is polycarboxylate water reducer CP1200.

[0063] Comparative Example 1 The invention discloses concrete, whose raw materials are cement, sand, aggregate, fly ash, water, slow-release additive and water reducing agent.

[0064] The sustained-release adjuvant is prepared in Preparation Example 11, and the water reducer is 2-acrylamido-2-methylpropanesulfonic acid.

[0065] The preparation method is as follows: Mix 21 kg of water reducer with 2540 kg of water to make mixing water; The mixing water is then stirred and evenly mixed with 4500kg of cement, 8800kg of sand, 13200kg of aggregate, 3380kg of fly ash and 380kg of slow-release additive to obtain concrete.

[0066] Comparative Example 2 The invention discloses concrete, whose raw materials are cement, sand, aggregate, fly ash, water, slow-release additive, paraffin powder and water reducing agent.

[0067] The sustained-release aid was prepared in Preparation Example 11, and the wax water reducer was 2-acrylamido-2-methylpropanesulfonic acid. The particle size of the paraffin powder was 60 μm, and the melting point was 42±2°C.

[0068] The preparation method is as follows: Mix 21 kg of water reducer with 2540 kg of water to make mixing water; The mixing water is then stirred and mixed evenly with 4500 kg of cement, 8800 kg of sand, 13200 kg of aggregate, 3380 kg of fly ash, 380 kg of slow-release additive and 96.7 kg of wax powder to obtain concrete.

[0069] Comparative Example 3 The invention discloses concrete, whose raw materials are cement, sand, aggregate, fly ash, water, slow-release additive, ferric nitrate powder and water reducing agent.

[0070] The sustained-release adjuvant was prepared in Preparation Example 11, the wax water reducer was 2-acrylamido-2-methylpropanesulfonic acid, and the particle size of the ferric nitrate powder was 500 nm.

[0071] The preparation method is as follows: Mix 21 kg of water reducer with 2540 kg of water to make mixing water; The mixing water is then stirred and evenly mixed with 4500 kg of cement, 8800 kg of sand, 13200 kg of aggregate, 3380 kg of fly ash, 380 kg of slow-release additive and 503.2 kg of ferric nitrate powder to obtain concrete.

[0072] Comparative Example 4 A concrete with low hydration heat peak value, which differs from Example 1 in that the phase change blocker is prepared according to Preparation Example 2.

[0073] Comparative Example 5 A concrete with low hydration heat peak value, which differs from Example 1 in that the phase change blocker is prepared according to Preparation Example 5.

[0074] The concrete of Examples 1 to 16 and Comparative Examples 1 to 5 were subjected to a large volume pouring hydration heat peak test, a standard part strength test and a flaw detection test.

[0075] Large volume pouring hydration heat peak test: A 2m×2m×2m pouring space is built by templates. The pouring space is divided into three layers above, middle and below. Each layer is divided into 9 grids, with a total of 27 grid spaces of the same size. Vertical threaded steel is used as a support and steel wire is used for binding. A temperature sensor is placed in the center of the 27 grid spaces. The temperature sensor is connected to a computer to record the temperature in real time. The freshly prepared concrete is poured into the pouring space, and intermittent vibration is performed during the pouring process. After the pouring is completed, the concrete temperature is recorded from 0 to 120h. The highest temperature value recorded by the 27 temperature sensors is the hydration heat peak value; the recording time is the time when the hydration heat peak value appears; the temperature curve is detected by the temperature sensor that detects the hydration heat peak value; the interval time from the point of hydration heat peak appearance to the time when the hydration heat temperature drops by 3.5℃ is recorded as the duration of the hydration heat peak value.

[0076] In the actual production process, the temperature of water used for concrete mixing is determined according to the current water supply conditions and can be less than 25°C. Here, the water used for concrete mixing in the large-volume pouring hydration heat peak test is provided by the same water tank, and the water level is 16°C.

[0077] Standard parts strength test: Preparation, curing and 28-day compressive strength test of concrete specimens were carried out according to the method in GB 50081-2019.

[0078] The test results are shown in Table 2 below.

[0079] Table 2. Test results of Examples 1 to 16 and Comparative Examples 1 to 5 Combining Table 1 and Table 2, by comparing Example 1 with Comparative Examples 1 to 3, it can be seen that the peak value of hydration heat of Example 1 is significantly lower than that of Comparative Examples 1 to 3, the peak time of hydration heat appears later than that of Comparative Examples 1 to 3, the peak duration of hydration heat becomes longer, and the 28-day compressive strength is improved.

[0080] The difference between Example 1 and Comparative Examples 1 to 3 is that the phase change blocker used is prepared by Preparation Example 1, the peak value of concrete hydration heat is 50-60°C, and during the release of concrete hydration heat, after the concrete is higher than the melting point of paraffin, the paraffin in the phase change blocker of Example 1 melts to store hydration heat; at the same time, as the paraffin melts, it slowly releases ferric nitrate powder through liquid surface contact, and the ferric nitrate dissolves in the liquid of the concrete and reacts with calcium hydroxide to produce ferric hydroxide precipitate and calcium nitrate, reducing the alkali content in the liquid phase of the concrete and increasing the calcium ion concentration in a short period of time, thereby inhibiting the hydration reaction rate, weakening the hydration heat peak without reducing the total amount of hydration heat, and smoothing the hydration heat curve. In addition, the ferric hydroxide precipitate can also seal the gaps in the concrete, thereby enhancing the strength of the final concrete.

[0081] In summary, in Example 1, the hydration heat curve is smoothed by storing hydration heat and slowing down the hydration heat reaction rate in the short term, so that the peak hydration heat of the concrete of the present application is reduced, and the possibility of cracks and fissures caused by excessive stress in the concrete body when the hydration heat peak is reached after large-volume pouring of the concrete of the present application is reduced, and the strength of the final concrete can also be enhanced.

[0082] By comparing Comparative Example 4, Example 2, Example 3, and Comparative Example 5, it can be seen that Examples 2 to 3 are similar to Example 1, and the peak hydration heat of Examples 2 to 3 is significantly lower than that of Comparative Example 1, the time of occurrence of the peak hydration heat is delayed compared with that of Comparative Example 1, and the duration of the peak hydration heat is prolonged; while the peak hydration heat of Comparative Examples 4 and 5 did not show a significant decrease. Therefore, in the present application, the phase change blocker needs to control the mass ratio of paraffin wax to ferric nitrate powder to be 1:(5 to 5.4) in order to play a role in reducing the peak hydration heat.

[0083] Comparing Example 1 and Example 4, the phase change blocker in Example 4 is obtained by directly mixing molten paraffin and ferric nitrate. During the preparation process, ferric nitrate is easily oxidized and unevenly dispersed, resulting in poor effect of the phase change blocker. The peak hydration heat of Example 4 is higher than that of Example 1, and the 28-day compressive strength of Example 4 is lower than that of Example 1.

[0084] Comparing Example 1 with Examples 5-6, it can be seen that the peak hydration heat of Example 1 is lower than that of Examples 5-6, and the 28-day compressive strength of Example 1 is greater than that of Examples 5-6; Comparing Example 1 with Examples 7-8, it can be seen that the peak hydration heat of Example 1 is lower than that of Examples 7-8, and the 28-day compressive strength of Example 1 is greater than that of Examples 7-8; Therefore, when the particle size of the phase change blocker in this application is controlled to 60μm and the particle size of the iron nitrate powder of the phase change blocker is controlled to 500nm, the hardness and granulation of the obtained phase change blocker are better, and the release time and rate of iron nitrate are better, and the obtained concrete has a low hydration heat peak and higher strength.

[0085] By comparing Example 1 and Example 15, it can be seen that Example 1 adds a slow-release adjuvant to the raw materials compared with Example 15. In Example 1, the slow-release adjuvant first slowly releases β-cyclodextrin and then releases zinc carbonate in the concrete. β-cyclodextrin chelates with calcium ions, prolongs the initial and final setting times of the concrete, prolongs the window period for the concrete to quickly conduct heat outward before solidification, reduces the temperature before concrete solidification, reduces the hydration heat peak, and thus reduces the possibility of cracks or cracks in large-volume concrete castings; then zinc carbonate can react with calcium hydroxide to reduce the alkali content in the concrete, reduce the alkali-aggregate reaction, and precipitate calcium ions at the same time, thereby reducing the concentration of calcium hydroxide, the hydration reaction product of tricalcium silicate and dicalcium silicate, and thus promotes the hydration reaction. Therefore, the hydration heat peak of Example 1 is lower than that of Example 15, and the 28-day compressive strength of Example 1 is higher than that of Example 15.

[0086] The ratio of β-cyclodextrin and zinc carbonate in the sustained-release adjuvant will also affect the hydration heat peak and strength of the concrete. By comparing Example 1 and Examples 9 to 12, it can be seen that the ratio of β-cyclodextrin and zinc carbonate in the sustained-release adjuvant used in the concrete is different, wherein the hydration heat peaks are from low to high in Example 1, Example 10, Example 9, Example 11, and Example 12, and the 28-day compressive strengths are from large to small in Example 1, Example 10, Example 9, Example 11, and Example 12. Therefore, in the present application, the mass ratio of β-cyclodextrin and zinc carbonate in the sustained-release adjuvant is controlled to be 7:(1.8-2.4), and the obtained concrete has a lower hydration heat peak and better strength.

[0087] By comparing Example 1 and Example 16, it can be seen that the peak hydration heat of Example 1 is lower than that of Example 16, and the 28-day compressive strength of Example 1 is greater than that of Example 16. The reason is that the water reducer in the raw material of Example 1 is an amino water reducer, and the amino water reducer enhances the fluidity of the concrete while keeping the water consumption of the concrete unchanged, which is beneficial to reduce the internal bubble cavity when pouring a large volume of concrete, and improve the strength of the concrete. In addition, the amino water reducer can also play a retarding role and reduce the peak hydration heat of the concrete.

[0088] By comparing Comparative Example 1 and Examples 13 to 14, it can be seen that the peak hydration heat of Examples 13 to 14 is significantly lower than that of Comparative Example 1, the time of occurrence of the peak hydration heat is delayed compared with that of Comparative Example 1, the duration of the peak hydration heat is prolonged and the 28-day compressive strength is improved. Therefore, when the mass ratio of cement, sand, aggregate, fly ash, water and phase change blocker in the concrete raw materials of the present application is controlled to be (300 to 500): (800 to 900): (1100 to 1400): (300 to 350): (200 to 280): (45 to 63), the obtained concrete has low hydration heat and good strength.

[0089] Embodiment 17 As attached Figure 1 As shown, a steel-concrete composite beam comprises a beam box 1 and a beam plate 2 fixed on the upper surface of the beam box 1.

[0090] The beam box 1 is a hollow steel box, the interior of which is provided with reinforcing strips according to actual needs, and concrete blocks for counterweight are poured inside.

[0091] The beam slab 2 is a concrete reinforced steel structure, which is obtained by pouring concrete and solidifying and curing it on the steel cage.

[0092] Shear connectors 3 such as bolts, channel steels, and bent bars are also fixed to the surface of the beam box 1 . The shear connectors 3 are wrapped by the concrete poured by the beam slab 2 so as to be buried in the beam slab 2 .

[0093] The concrete used for pouring the beam and slab 2 is one of the concretes in Examples 1 to 16.

[0094] The steel-concrete composite beam of the present application has a low hydration heat peak during the pouring process of the beam slab, which reduces the generation of internal fine cracks, has fewer internal structural defects, and has good ductility during seasonal temperature changes. In addition, the yield is high, the production efficiency is high, and the cost is reduced.

[0095] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed. However, as long as the modifications are within the scope of protection required by the present application, they shall be protected by the patent law.

Claims

1. A concrete with low hydration heat peak, characterized in that: Including the following raw materials by mass: 300~500 parts of cement, 800~900 parts of sand, Aggregate 1100~1400 parts, 300~350 parts of fly ash, 200~280 parts of water, 45~63 parts of phase change blocker, The phase change blocker is obtained by mixing and granulating paraffin wax and ferric nitrate powder. The melting point of the paraffin wax is 42±2° C., and the mass ratio of the paraffin wax to the ferric nitrate powder is 1:(5~5.4).

2. The concrete with low hydration heat peak according to claim 1, characterized in that: The preparation method of the phase change blocker is as follows: Weigh ferric nitrate powder and paraffin powder according to the mass ratio, stir and mix to obtain a mixed raw material; The mixed raw material and hexane are mixed and then ball-milled to obtain a ball-milled slurry; The ball mill slurry is spray dried and granulated to obtain a phase change inhibitor with uniform particle size distribution.

3. The concrete with low hydration heat peak according to claim 1, characterized in that: The particle size of the iron nitrate powder is 500 nm.

4. The concrete with low hydration heat peak according to claim 1, characterized in that: The phase change blocker has a particle size of 50-80 μm.

5. The concrete with low hydration heat peak according to claim 1, characterized in that: The invention also comprises 35 to 41 parts of a sustained-release enhancer, wherein the sustained-release enhancer is a core-shell structure, wherein the shell is β-cyclodextrin, and the shell is zinc carbonate.

6. The concrete with low hydration heat peak according to claim 1, characterized in that: The mass ratio of β-cyclodextrin to zinc carbonate in the sustained-release aid is 7:(1.8-2.4).

7. The concrete with low hydration heat peak according to claim 1, characterized in that: It also includes 1.8 to 2.3 parts of amino water reducer.

8. A steel-concrete composite beam, characterized in that: It comprises a steel beam box (1) and a concrete beam slab (2), wherein the concrete is a concrete with a low hydration heat peak value as claimed in any one of claims 1 to 7.